Academic burnout in terms of perfectionism and self-efficacy - Sari, Liana; Thahir, Andi; Reza, Faisal Adnan (Universitas Islam Negeri Raden Intan Lampung, 2024)
The study aims to determine whether there is a relationship between perfectionism and self-efficacy in academic burnout. The subjects of the study were high school students as well as boarding school students in the Bandar Lampung area. This type of research uses quantitative methods. Sampling using purposive sampling method with a total sample of 170 respondents. Data analysis used multiple linear regression analysis techniques with JASP. The results of this study indicate that there is a significant positive relationship between perfectionism and academic burnout with a correlation coefficient (R) of 0.568 with a significance of 0.001 (p<0.01). The relationship between negative self-efficacy and academic burnout has a significant negative relationship with a correlation coefficient (R) of -0.399 with a significance of 0.001 (p<0.01). The effective contribution of the perfectionism variable to the academic burnout variable is 28%. Meanwhile, the effective contribution given by self-efficacy to the academic burnout variable is 5%. That is, the conclusion is obtained that the higher the perfectionism, the higher the academic burnout, and vice versa. However, the higher the self-efficacy, the lower the academic burnout, and vice versa.